Integrating ecosystem services into effectiveness assessment of ecological restoration program in northern China's arid areas: Insights from the Beijing-Tianjin Sandstorm Source Region. (June 2018) - Jiang, Chong; Nath, Reshmita; Labzovskii, Lev; Wang, Dewang
Highlights: We applied several bio-physical models to quantify ecosystem services in a spatially explicit manner. Farmland and desert shrinkages, woodland expansion, and urban sprawl were observed during 2000–2010. Provisioning service (food production) increased significantly during 2000–2010. Synergies existed among the regulating and provisioning ecosystem services. Abstract: The Beijing–Tianjin Sandstorm Source Region (BTSSR) is the main sandstorm source area in northern China, which plays a crucial role in ecological safety and sustainable development of Beijing and the neighbouring areas. As a result of climate change, ecological restoration and anthropogenic activities, the ecosystem in the BTSSR has experienced substantial changes over the recent decades. The main objective of this study is to quantify the dominant ecosystem services from 2000 to 2010, based upon observations and biophysical models. Furthermore, we investigated the role of climatic variability and ecological restoration program in vegetation activity and ecosystem services. Although the slight increase, both in precipitation and temperature during 2000–2010 and despite the implemented ecological rehabilitation, several drought events offset the ecological rehabilitation program. During 2000–2010, both the overall soil conservation and hydrological regulation functions were slightly enhanced. The carbon sequestration remained stable and food production has sharply increased. The increasing rainfall erosivity has intensified water erosion, whereas the reduction in wind speed weakened wind erosion and thereby reduced the sandstorm events. Vegetation restoration induced by the climatic variability and ecological program has also played a positive role in soil conservation and hydrological regulation enhancement. The spatial correlation analysis indicated the synergies between multiple regulating ecosystem services. Moreover, a synergy between food yield and vegetation carbon sequestration (biomass production) has been identified as well. The experience of ecological rehabilitation and ecosystem change in the BTSSR has exemplified the ecological conservation should take climatic variability into account, and facilitate the synergies on multiple ecosystem services in order to maximize the ecosystem's benefits to human well-being.